Effect of chlorine-repulsive molecular fragments on photocatalytic seawater splitting performance of BiVO4 for oxygen evolution. (19th March 2023) - Qv, Yang; Xv, Ruichao; He, Qiuchen; Zhao, Ziming; Zhou, Feng; Zhan, Su
Abstract: Photocatalysis to produce clean energy by splitting seawater have great practical importance for dealing with the energy crisis. However, seawater contains many Cl − ions whose oxidation competes with the oxygen evolution reaction. In this work, we present a photocatalyst modified with S-containing molecular fragments on the surface to improve its efficiency in the oxygen evolution reaction in seawater splitting. We found that the oxygen evolution performance of BiVO4 modified with S-containing molecular fragments was 1.7 times higher than the unmodified material. Based on this finding, the modification didn't affect the light absorption and charge separation efficiency of BiVO4, but lead to a marked (83.6%) decrease of the effective chlorine concentration in the reactor after photocatalytic reaction. The results indicate that the surface modification with S-containing molecular fragments is an effective method to repel chlorine. This work provides a useful reference to improve the efficiency of photocatalysts in overall seawater splitting. Graphical abstract: Image 1 Highlights: Constructed BiVO4 is modifying with S-containing molecular fragments. S-containing molecular fragments can effectively inhibit the occurrence of Cl − oxidation. BiVO4 /S have a better performance of the oxygen production in photocatalytic seawater splitting.